1998
DOI: 10.1063/1.882131
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-Intensity Lasers: Physics of the Extreme on a Tabletop

Abstract: Over the past ten years, laser intensities have increased by more than four orders of magnitude to reach enormous intensities of 1020 W/cm2. The field strength at these intensities is on the order of a teravolt per centimeter, or a hundred times the Coulombic field binding the ground state electron in the hydrogen atom. The electrons driven by such a field are relativistic, with an oscillatory energy of 10 MeV. At these intensities, the light pressure, P = I/c, is extreme, on the order of giga- to terabars. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
264
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(267 citation statements)
references
References 27 publications
1
264
0
2
Order By: Relevance
“…Studying the propagation of nonlinear plasma electromagnetic waves being of great practical interest due to the progress in laser technologies [84,85] has shown that powerful ultrashort laser pulses propagating in a plasma can accelerate the plasma electrons to ultra-relativistic energies (so called "laser wakefield acceleration") [86][87][88][89]. Considering the problem of powerful ultrashort laser pulse interaction with a plasma based on numerical simulations, a model for a strongly nonlinear regime of interaction of intense laser pulses with plasmas has been proposed.…”
Section: Channeling In a Plasma-ion Cavitymentioning
confidence: 99%
“…Studying the propagation of nonlinear plasma electromagnetic waves being of great practical interest due to the progress in laser technologies [84,85] has shown that powerful ultrashort laser pulses propagating in a plasma can accelerate the plasma electrons to ultra-relativistic energies (so called "laser wakefield acceleration") [86][87][88][89]. Considering the problem of powerful ultrashort laser pulse interaction with a plasma based on numerical simulations, a model for a strongly nonlinear regime of interaction of intense laser pulses with plasmas has been proposed.…”
Section: Channeling In a Plasma-ion Cavitymentioning
confidence: 99%
“…Last years CPA technique permitted the production of subpicosecond laser pulses of multiterawatt power with peak intensities exceeding 10 20 W/cm 2 [2]. With intensities as such we practically have to do with a new interaction range of laser radiation with matter, where the role of the nonlinear effects is often essential.…”
Section: Introductionmentioning
confidence: 99%
“…One of these advances is the implementation of the Chirped Pulse Amplification (CPA) technique [1] which has created new opportunities in the domain of ultra-intense and ultrafast laser physics. The interactions of ultra high-intensity laser pulses with matter have opened the field of optics in relativistic plasmas, a new topic of high-field science presented in comprehensive reviews [2,3]. Indeed, intense lasers have been used to accelerate beams of electrons [4] and protons [5] to energies of several megaelectronvolts in distances of only microns.…”
Section: Introductionmentioning
confidence: 99%